Análise citogenética de escorpiões da fauna brasileira com ênfase nas sequências de DNA repetitivo - Lima, Juliana Figueiredo de [UNIFESP] (2017)
In this work, 10 scorpions species were analyzed analyzed, aiming to understand processes involved in the origin and maintenance of interspecific and intraspecific chromosomal variability and the mechanisms related to the high rates of chromosomal rearrangements. To this end, species of the families Buthidae and Chactidae, which have differences in relation to the type of chromosomes and the presence / absence of rearrangements, were cytogenetically characterized regarding to the distribution and amount of heterochromatin and repetitive DNA sequences (multigenic families and / or satellite DNA). The study of bisexual populations of T. serrulatus revealed a diploid number (2n = 12) similar to that previously described for parthenogenetic populations. However, the identification of specific chromosomal region (28S rDNA) showed differences between males and females, which presented, respectively, two and one chromosomes carrying the ribosomal gene. This result points to the presence of a ZZ / ZW sex chromosome system in this species. The analysis of nine other scorpions of the families Chactidae and Buthidae showed that in the cactids the diploid numbers are higher (2n = 50, 2n = 36 and 2n = 30) than in the buthids (2n = 6, 2n = 10, 2n = 14, 2n = 18, 2n = 26) and that the species have monocentric chromosomes. Despite the differences in diploid number, the localization of rDNA sites were conserved in the species Brotheas amazonicus and Chactopsis amazonica (Chactidae) and Tityus apiacas (Buthidae). The localization of repetitive sequences through the Cot-1 technique and constitutive heterochromatin by C-band and DAPI-after FISH indicate that there is no a frequent of repetitive DNA distribution in the chromosomes. This data reveals that the identification of repetitive DNA sequences in scorpion chromosomes need to be analyzed with different cytogenetic approaches. In addition, a more comprehensive knowledge of the quantity and types of repetitive sequences present in the genome of scorpions is needed to ascertain whether there is a relationship between the occurrence of these regions with rates of chromosomal rearrangement found in the species.